Dopamine coated polycaprolactone nanospheres for prochloraz delivery to improve antifungal activity and environmental safety - Junwei Yao; Qian Wang; Chunxin Wang; Hong Qi; Qingshan Shi; Jingxia Liu; Jin Feng; Ping Yang; Manli Yu; Xiaobao Xie (Journal of Environmental Chemical Engineering, 2026)

Pollution characteristics, sources and health risk of potentially toxic elements in urban road dust from different functional areas in Hefei, China - Jinhua Wang; Jing Liang; Manli Zhu; Jincheng Ni; Yu Liang; Jian Huang; Tao Luo; Bingbing Zhao; Shanshan Xi; Kun Wang; Liangchen Xu (Environmental Geochemistry and Health, 2026)

Optimizing submerged plant restoration in eutrophic lakes: Insights from plant community structure and water depth - Manli Xia; Wei Li; Yongwei Zhi; Yu Cao (Journal of Environmental Management, 2026)

Distinct Adaptive Strategies of Three Floating-Leaved Species in Nymphoides Across Water Depth Variations: Evidence from Morphology, Hydraulics and Photosynthesis - Wei Liu; Manli Xia; Charity Mangoi; Daomin Cheng; Chaoyu Tian; Wei Li; Longyi Yuan; Yu Cao (Wetlands, 2026)

Comparative study on the ecotoxicity of nanoformulated and conventional emamectin benzoate to Raphidocelis subcapitata: A mechanistic disparity analysis - Jin Yang; Yiming Chang; Ruiqiang Fu; ManLi Yu; Lan Zhang; Liangang Mao; Lizhen Zhu; Chi Wu; Yanning Zhang; Xingang Liu (Environmental Pollution, 2026)

Alkyl-modified polyacrylic acid hydrogel tablets for Targeted retention and reduced droplets drift of glyphosate isopropylamine salt - Yingxi Zhang; Hanghang Zhang; Chong Cao; Pengyue Zhao; Mingming Yin; Manli Yu; Qiliang Huang; Lidong Cao (Journal of Cleaner Production, 2025)

Corilagin inhibits the proliferation of vascular smooth muscle and excessive matrix deposition following vascular injury via the MAPK pathway - Wei Zhang; Manli Yu; Ye Cao; Liuliu Feng; Yu Wang (Journal of Muscle Research and Cell Motility, 2025)

Differential roles of nitrogen and phosphorus in petroleum hydrocarbon biodegradation: Metatranscriptomic insights from soil bioremediation - Yawen Ou; Chun Zhang; Manli Wu; Ying Yu; Xuhong Zhang; Min Hu; Huan Gao; Xijun Wu (Journal of Environmental Chemical Engineering, 2025)

Ratiometric fluorescence analysis of tetracycline by dual-ligand europium-based metal-organic framework - Yating Zhong; Keying Zhang; Xinru Wang; Haibo Liang; Ying Yu; Manli Guo; Yujuan Cao; Bixia Lin (Food Chemistry, 2025)

Influence mechanisms underlying the degradation of petroleum hydrocarbons in response to various nitrogen dosages supplementation through metatranscriptomics analysis - Yawen Ou; Manli Wu; Ying Yu; Zeliang Liu; Haoxuan Kang; Min Hu; Chun Zhang; Xing Chen (Journal of Hazardous Materials, 2025)

Tebuconazole residue in wheat and food risks: Comparison among nano and conventional formulations - Kuan Wang; Manli Yu; Haixiang Gao; Xinglu Pan; Xiaohu Wu; Jun Xu; Yongquan Zheng; Fengshou Dong (Food Chemistry, 2025)

Long-term exposure to ambient air pollution and the incidence of systemic lupus erythematosus - Lihong Ye; Ding Ye; Yu Qian; Jiayu Li; Bin Liu; Jiacheng Ying; Manli Wang; Hao Lin; Jing Guo; Xiaohui Sun; Zhixing He; Chengping Wen; et al. (Chemosphere, 2025)

Photo-responsive supramolecular hydrogels to enhance pesticide bioavailability through multiple structural transformations - Hanghang Zhang; Yingxi Zhang; Manli Yu; Chong Cao; Pengyue Zhao; Qiliang Huang; Lidong Cao (Chemical Engineering Journal, 2025)

Construction of Zinc-based metal-organic frameworks for visual ratiometric fluorescence detection of tetracycline - Yating Zhong; Haocheng Gao; Jingqi Yang; Xinru Wang; Ying Yu; Yujuan Cao; Manli Guo; Bixia Lin (Analytica Chimica Acta, 2025)

A comprehensive evaluation of bioremediation effects of oil-contaminated soils using various dosages of exogenous nitrogen supplementation: TPH removal, ecological toxicity, and microecological response - Ying Yu; Yawen Ou; Manli Wu; Xuhong Zhang; Zeliang Liu (Journal of Environmental Chemical Engineering, 2024)

Microbial community diversity analysis of kiwifruit pollen and identification of potential pathogens - Jiaqi Yang; Manli Yao; Dan Zhang; Yu Zhao; Guitian Gao (Antonie van Leeuwenhoek, 2024)

Tracing potentially toxic elements in button mushroom cultivation and environmental implications: Insights via stable lead (Pb) isotope analysis - Xun Liu; Junjie Yu; Xueping Lu; Manli Yang; Yazhou Liu; Hui Sun; Ying Ni; Guo Lin; Chuansheng Wu; Jun Tang (Journal of Cleaner Production, 2024)

Nitrogen utilization efficiency assessment during bioremediation of petroleum-contaminated loess soils: insights from metagenomic analysis - Yawen Ou; Manli Wu; Ying Yu; Zeliang Liu; Yu Zhang; Ning Yi (Journal of Hazardous Materials, 2024)

Oral carbon dot nanozymes with red fluorescence and superoxide dismutase-like activity for colitis bioimaging and inflammation management - Mingxin Zhang; Yunlong Liang; Yanan Zhang; Lingmin Zhang; Ning Wang; Ying Zhou; Yufeng Wang; Manli Cui; Zhaoxiang Yu; Mingzhen Zhang; Yana Ma (Chemical Engineering Journal, 2024)

Low dose phosphorus supplementation is conducive to remediation of heavily petroleum-contaminated soil—From the perspective of hydrocarbon removal and ecotoxicity risk control - Yawen Ou; Manli Wu; Ying Yu; Zeliang Liu; Ting Zhang; Xuhong Zhang (Science of The Total Environment, 2024)

Hydrophobic sisal cellulose paper-based TENG for collecting rain energy and raindrop-based sensor - Yating Pan; Ming Li; Yuxiang Lu; Manli Lu; Bin Guo; Xianming Liu; Kaiyou Zhang; Yu Wang; Liang Feng; Aimiao Qin (Chemical Engineering Journal, 2024)

Temporal variations of stable isotopic compositions in atmospheric water vapor on the Southeastern Tibetan Plateau and their controlling factors - Manli Chen; Jing Gao; Lun Luo; Aibin Zhao; Xiaowei Niu; Wusheng Yu; Yigang Liu; Gebanruo Chen (Atmospheric Research, 2024)

Chitooligosaccharide modified pesticide-loaded polyurethane microcapsules to mitigate drought stress in wheat - Ge Chen; WenJie Shangguan; HuiPing Chen; ChunLi Xu; Muhammad Bilal; PengYue Zhao; Chong Cao; ManLi Yu; QiLiang Huang; LiDong Cao (Chemical Engineering Journal, 2024)

Preclinical evaluation of RQ3013, a broad-spectrum mRNA vaccine against SARS-CoV-2 variants - Shudan Tan; Jinghua Zhao; Xue Hu; Yufeng Li; Zihan Wu; Guoliang Lu; Zhaoli Yu; Binhe Du; Yan Liu; Li Li; Yuchen Chen; Ye Li; et al. (Science Bulletin, 2023)

Sodium alginate-based composite microspheres for controlled release of pesticides and reduction of adverse effects of copper in agricultural soils - Yu Du; Qizhen Zhang; Manli Yu; Bin Jiao; Fuliang Chen; Mingming Yin (Chemosphere, 2023)

IL-17A promotes endothelial cell senescence by up-regulating the expression of FTO through activating JNK signal pathway - Na Li; Runan Luo; Wenlong Zhang; Yu Wu; Chaojie Hu; Manli Liu; Diya Jiang; Ziran Jiang; Xinxin Zhao; Yiping Wang; Qing Li (Biogerontology, 2023)

A Facile, Label-free and Versatile Fluorescence Sensing Nanoplatform Based on Titanium Carbide Nanosheets for the Detection of Various Targets - Meishuang Liang; Bixia Lin; Zhijiao Tang; Li Zhang; Manli Guo; Yujuan Cao; Yumin Wang; Ying Yu (Journal of Fluorescence, 2022)

Factors Influencing Alzheimer’s Disease Risk: Whether and How They are Related to the APOE Genotype - Rong Zhang; Xiaojiao Xu; Hang Yu; Xiaolan Xu; Manli Wang; Weidong Le (Neuroscience Bulletin, 2022)
Alzheimer's disease (AD) is the most prevalent neurodegenerative disease featuring progressive cognitive impairment. Although the etiology of late-onset AD remains unclear, the close association of AD with apolipoprotein E (APOE), a gene that mainly regulates lipid metabolism, has been firmly established and may shed light on the exploration of AD pathogenesis and therapy. However, various confounding factors interfere with the APOE -related AD risk, raising questions about our comprehension of the clinical findings concerning APOE . In this review, we summarize the most debated factors interacting with the APOE genotype and AD pathogenesis, depict the extent to which these factors relate to APOE -dependent AD risk, and discuss the possible underlying mechanisms.

Use of Clinoptilolite to Enhance Rice Sink–Source Traits and Water Productivity Under Alternate Wet–Dry Irrigation - Hongyang Chen; Yidi Sun; Wenxiao Xie; Qi Wu; Daocai Chi; Guangxing Yu; Jingui Dai; Manli Zhang; Changhua Wang; Zhiqiang Tang (Journal of Soil Science and Plant Nutrition, 2021)

Consumer-driven nutrient release to the water by a small omnivorous fish enhanced ramet production but reduced the growth rate of the submerged macrophyte Vallisneria denseserrulata (Makino) Makino - Jinlei Yu; Manli Xia; Yanyan Zhao; Hu He; Baohua Guan; Feizhou Chen; Zhengwen Liu; Erik Jeppesen (Hydrobiologia, 2021)

Efficient electrokinetic remediation of heavy metals from MSWI fly ash using approaching anode integrated with permeable reactive barrier - Huilin Li; Yi Zheng; Lin Yu; Huirong Lin; Manli Zhang; Binquan Jiao; YanChyuan Shiau; Dongwei Li (Environmental Science and Pollution Research, 2021)

Density-dependent effects of omnivorous bitterling (Acheilognathus macropterus) on nutrient and plankton communities: implications for lake management and restoration - Jinlei Yu; Manli Xia; Wei Zhen; Ruijie Shen; Hu He; Baohua Guan; James J. Elser; Zhengwen Liu (Hydrobiologia, 2020)

A small omnivorous bitterling fish (Acheilognathus macropterus) facilitates dominance of cyanobacteria, rotifers and Limnodrilus in an outdoor mesocosm experiment - Jinlei Yu; Manli Xia; Ming Kong; Hu He; Baohua Guan; Zhengwen Liu; Erik Jeppesen (Environmental Science and Pollution Research, 2020)

Tunable and Nontoxic Fluorescent Probes Based on Carbon Dots for Imaging of Indole Propionic Acid Receptor in Plant Tissues in Situ - Bixia Lin; Ying Yu; Fangfei Liu; Yujuan Cao; Manli Guo (Journal of Fluorescence, 2017)

Soluble receptor for advanced glycation end products mitigates vascular dysfunction in spontaneously hypertensive rats - Yu Liu; Manli Yu; Le Zhang; Qingxin Cao; Ying Song; Yuxiu Liu; Jianbin Gong (Molecular and Cellular Biochemistry, 2016)